PENGARUH KOMPENSASI, KOMPETENSI, DAN PENGALAMAN KERJA TERHADAP KINERJA KRU BUS TRANSJATIM KORIDOR 5 RUTE SURABAYA – BANGKALAN - Muhammad Rafif Aledery Wicaksana; Bowo Santoso (MANAJEMEN DEWANTARA, 2025)
This study aims to analyze the effect of compensation, competence, and work experience on the performance of Transjatim bus crews operating on Corridor 5, Surabaya – Bangkalan route. The research adopts a quantitative approach with a survey method. Data were collected from 40 respondents using questionnaires and analyzed via Partial Least Squares (PLS) with the assistance of SmartPLS 3.0 software. The results show that all three independent variables compensation, competence, and work experience have a positive and significant impact on performance. Compensation emerged as the most influential factor, with salary serving as the primary indicator. Meanwhile, competence and work experience also contribute positively and significantly. These findings suggest that management should place greater emphasis on employee welfare and skill development to support performance improvement in public transportation services.